Managing agricultural water resources: Addressing the complexity of innovation, social perspectives, and water governance in Sri Lanka - Jayasiri, Maveekumbure Manthreethilaka Jayasiri Gamaralalage Chathuri; Yadav, Sudhir; Dayawansa, Nandani Dhammika Kumari; Ingold, Karin (Wiley, 2022)
Irrigation plays a vital role in world food security. Agriculture accounts for 70% of freshwater withdrawals worldwide, and the figure is even higher in developing countries like Sri Lanka. The rapid expansion of anthropogenic activities, together with the anticipated climatic risks associated with them, is exacerbating the problem of increasing agricultural water demand. Although it has been recognized for decades, improving irrigation water‐use efficiency and water productivity is still considered the most realistic option for addressing the challenge of sustainable management of water resources. However, adoption of recommended water‐efficient technologies and concepts remains elusive in practice, highlighting the gaps created by failing to consider social perspectives in developing water management strategies. As a result, the effectiveness of water governance has often been questioned in terms of performance and adoption of innovative technologies. This paper reviews and discusses the complexity of innovation through a technical, social, and institutional lens by reviewing available research on Sri Lanka's river basins and presents a perspective on opportunities for improving irrigation water management.